The Evidence for Selective Loss of Otolithic Function - Curthoys, Ian S.; Burgess, Ann M.; Manzari, Leonardo (Seminars in Neurology, 2020)
Recent advances in vestibular testing now permit functional testing of all peripheral vestibular sense organs (all three semicircular canals, utricle, and saccule). This makes it possible to identify patients with isolated dysfunction of the utricle or saccule, even though parallel pathways for vestibular information are ultimately integrated centrally. Selective, isolated unilateral loss of utricular function as measured by ocular vestibular-evoked myogenic potentials (VEMPs) has been observed in patients with normal semicircular canal function as measured by the video head impulse test of all six semicircular canals, and normal bilateral saccular function as determined by symmetrical cervical VEMPs. How these patients present clinically and how they recover is discussed and contrasted with acute vestibular neuritis. In some patients, the unilateral loss of otolith organ (utricle or saccule) function persists and yet the patient recovers functionally to their usual lifestyle. Until the testing of all peripheral vestibular sense organs is routine, the frequency of isolated loss of otolith function cannot be gauged.
Keywords: vestibular; oVEMP; cVEMP; utricular; saccular